The impact of public participation on the perception of service quality in local government in Southern Thailand - Suphattanakul, Onuma (2014)
Local government in Thailand is facing many hindrances in providing service quality to the public. Among the critical factor noted is poor public participation in local government decision-making process. Therefore, this study evaluates the degree of public participation in the decision-making process in local government in Southern Thailand. The impact of public participation on the perception of service quality in local government was also examined. In addition, this study also compares the differences in the perception of service quality between customers and local government officials. Lastly, the differences in customers’ perception of service quality between types of municipality and locations of the municipality is also reviewed. This research employs both quantitative and qualitative methods. The target population consisted of local government officials who were working as administrative officials, and customers who received the services of the local government. More than 600 questionnaires were collected from both customers and officials of over 200 municipalities in Southern Thailand. Twenty officials were interviewed to gather in-depth information. To analyse the data, independent t-test and ANOVA were used to test the differences between the groups while Pearson correlation analysis was used to test the relationship between the independent variables and the dependent variable. Linear regression analysis was used as appropriate statistical tool to test the hypotheses. The results showed that the degree of decision-making participation occurred at a high level in a goal setting process. There was a significant positive impact between public participation and the perception of service quality of the local government officials. In addition, it showed that the gap in the perception of service quality was higher for the customer group compared to that of the local government officials. Moreover, this study revealed that there were significant differences in customers’ perception of service quality between the types of municipality and the locations of the municipality. As such, in order to increase service quality, it is recommended for all types of municipalities to increase efforts to enhance public participation in their decision-making process. This study contributes to the existing body of knowledge by integrating together the public management and the customer–oriented approaches in relation to the perception of service quality, which is based on the marketing approach.